Learning first, technology second in practice - Kolb, Liz; Kolb, Liz. (Portland, Oregon : International Society for Technology in Education, 2020)
'After observing teachers and students interact with technology over many years, Liz Kolb began to wonder: How do we move students from a high-attention, low-commitment to learning with digital devices to a high-attention, high-commitment to learning tasks? Her observations led her down a path of extensive research that informed the development of the Triple E Framework (covered in the 2017 ISTE book Learning First, Technology Second). Kolb found that teachers needed a framework based on good learning practices with technology rather than a focus on technology tools themselves. With this in mind, she developed the Triple E Framework, in which the learning goal - not the tool - is the most important element of a given lesson. Understanding how students learn is built into the Triple E Framework, allowing teachers to choose the tool and pedagogical strategies that best fit the learning goal. Ultimately, the Triple E Framework is meant to support the teacher in making choices with technology and instructional strategies based on the learning goal and the science of learning. For Learning First, Technology Second readers, this book will build on their knowledge, providing a brief overview as well as new research, scenarios, cases and ideas for using technology in education. For readers new to the framework, this book will provide all of the essential research and tools mentioned above, along with an overview of the framework, so they can apply what they learn without missing a beat'--
Includes bibliographical references and index.
Keywords: Educational technology; Education -- Effect of technological innovations on; Lesson planning